Key concepts in sociology - Braham, Peter (SAGE key concepts, 2013)
"Sociology consists of a myriad of frequently confusing concepts. Key Concepts in Sociology provides a comprehensive, lively and clearly-written guide to the most important concepts in the subject. It includes both what might be regarded as 'classic' sociological concepts, such as 'class', 'bureaucracy' and 'community', as well as subjects that have become increasingly prominent in recent times, such as 'celebrity', 'risk' and 'the body'."